Pembrolizumab-induced optic neuropathy – a case report - Daetwyler, Eveline; Zippelius, Alfred; Meyer, Peter; Läubli, Heinz (Frontiers in Immunology, 2023)
Background: Immune checkpoint inhibitor (ICI) treatment has become important for treating various cancer types, including Hodgkin’s lymphoma. However, ICI can overstimulate the immune system, leading to a broad range of immunological side effects, known as immune-related adverse events (irAEs). Here, we report a case of optic neuropathy caused by pembrolizumab. Case presentation: A patient with Hodgkin’s lymphoma received pembrolizumab every three weeks. Twelve days after the sixth cycle of pembrolizumab, the patient was admitted to the emergency department with blurred vision, visual field impairment and altered color perception affecting the right eye. The diagnosis of immune-related optic neuropathy was established. Pembrolizumab was stopped permanently and high-dose steroid treatment was immediately started. This emergency treatment led to a satisfactory binocular vision and an improvement of visual acuity testing results. After another 7 months, the left eye was affected with the same symptoms. At this time, only an extended immunosuppressive therapy consisting of high-dose steroid treatment, plasmapheresis, immunoglobulin treatment, retrobulbar injection of steroids and mycophenolate mofetil, successfully reduced the symptoms. Conclusions: This case highlights the need for prompt recognition and treatment of rare irAEs, such as optic neuropathy. Urgent treatment with initial high-dose steroid treatment is required to avoid persistent loss of visual acuity. Options for further treatment are mainly based on small case series and case reports. In our case, a retrobulbar injection of steroids in combination with mycophenolate mofetil showed significant success in treating steroid-refractory optic neuropathy.